Quality of service performances of three mobile ad hoc network protocols - Adam, Nabilah (2009)
Mobile Wireless Ad Hoc Networks (MANETs) is network without infrastructure, where every node functions as transmitter, router and data sink. Every node must discover its local neighbours and through them it will communicate to nodes that are out of its transmission range. The routing mechanisms in MANET are challenged by the interaction of three fundamental difficulties such as contention, congestion and node connectivity. Every ad hoc routing protocol has their own advantages based on the performances in the network. The thesis proposed to evaluate the Quality of Service (QoS) performances of three types MANET protocols. The protocols included the Dynamic Source Routing (DSR), Ad Hoc On-demand Distance Vector (AODV) and Temporally Ordered Routing Algorithm (TORA) protocol. The analysis had been done theoretically and through simulation using an Optimized Network Engineering Tools (OPNET) Modeler. Using OPNET Modeler software, these performances had been analyzed by the following metrics: packet delivery ratio, end-to-end delay, packet dropped, routing load and end-to-end throughput.